Contributing Factors of Non-Adherence to Treatment among the Patients with Type II Diabetes Mellitus - Bhattarai, B; Bista, B; Shrestha, S; Budhathoki, B; Dhamala, B (Journal of Manmohan Memorial Institute of Health Sciences, 2019)
Background: The Multiple therapeutic component and need for life long treatment makes diabetic adherence a difficult task. We took this study to identify the Non adherence Patient to the  Diabetic treatment, and to assess the contributing factors for non adherence.Methods: A four questions preformed questionnaire -the Morisky medication adherence scale (MMAS) and Structured questionnaire were used to assess the contributing factors of Non adherence to diabetic treatment in 214 patient with type 2 diabetes mellitus which was carried out on Kathmandu Diabetic and Thyroid Center, Alka Hospital and Endocrine Care Center, Kupandol following Probability simple random sampling technique.Results: A total of 55.14% of diabetic client were non adherent. Major contributing factor of non-adherence to diabetic treatment were ignorance for life style modification i.e.  83.78%. Among them, 59.48% didn't take the prescribed medicine in time ,most of them 85.71% didn't follow diabetic diet and less than half (46.61%) didn’t monitored blood glucose level regularly due to poor self discipline. Gender, occupation and educational status were the significant contributors to Non adherence.Conclusion: The findings showed high percentage of  non adherent  diabetic  client and enlighten the various factors causing non adherence. It focuses the need for one to one counselling and constant motivation frequently to ensure better adherence.